Indoor overheating and mitigation of converted lofts in London, UK. (July 2019) - Li, Xiaoyi; Taylor, Jonathon; Symonds, Phil
In the UK, there has been an increase in the number of loft conversions, driven by demands for increased floor areas of dwellings to accommodate more individuals or increase property values. While rooms directly underneath roofs are known to have increased overheating risks, there is little research available that quantifies this risk, and how to mitigate it cost-effectively. This paper seeks to evaluate overheating risks in loft conversions, using integrated environmental solutions virtual environment to dynamically simulate indoor temperatures in a semi-detached dwelling in London, UK, under current and future (2050s and 2080s medium and high emissions) climate scenarios. Adaptive overheating risk and energy consumption are calculated with and without passive overheating adaptations that reduce solar gains, increase ventilation, or add thermal insulation. Marginal abatement cost curves (MACC) are then used to select the most cost-effective adaptations based on installation and ongoing energy consumption costs. Results estimate 11, 340–12, 210 more summertime Category I overheating degree-hours for the loft than conventional bedrooms in the dwelling under the current climate; total category I loft overheating degree-hours may increase to 20, 319 by 2080. While external shutters and night-purge ventilation were the most effective at reducing overheating degree-hours (96% and 89%, respectively), the most cost-effective solutions considering capital and ongoing costs are ventilation strategies, including night-time purge ventilation, advance ventilation and cross ventilation. Passive adaptations are not capable of eliminating overheating entirely, and by the 2080s active cooling is likely to be required to maintain comfortable indoor conditions in lofts. Practical application : Converted lofts – present in 5.8% of English and 10.8% of London dwellings – are at significantly elevated risk of high indoor temperatures relative to conventional rooms. Passive adaptations such as ventilation and shading can effectively mitigate loft overheating until around 2080, after which active measures become necessary. When capital and ongoing costs are considered, the most cost-effective heat mitigating adaptations are night and advance ventilation and internal curtains/blinds. Heat mitigating adaptations for converted lofts should become mandatory, and such spaces should not be occupied by the vulnerable or elderly during hot weather.